OBSERVASI DAN ANALISIS INFRASTRUKTUR TEKNOLOGI INFORMASI (ITI)PT DIGITAL NUSANTARA - Fenny Purwani; Rendy Febriyana; Tiara Meftahul Jannah; Duwi Febyanti; Ilmiah Tanjung (CV. Denasya Smart Publisher, 2025)
Information Technology Infrastructure (ITI) plays a pivotal role in supporting operational excellence and digital transformation in modern enterprises. PT Digital Nusantara, a technology-driven company, has implemented various IT systems to optimize productivity, operational efficiency, and business competitiveness. This study aims to evaluate the IT infrastructure of PT Digital Nusantara through direct observation of physical facilities, software systems, network architecture, data security protocols, and IT human resources management. The findings reveal that while the company has developed a solid technological foundation, it still faces strategic challenges such as scalability limitations, insufficient system integration across departments, and the need to comply with international information security standards. This article suggests reinforcing cloud-based infrastructure, developing a long-term IT roadmap, and improving IT personnel capabilities through structured digital competency training.